Random deposition of particles with different angles - Vilas Boas, Amanda Carvalho Augusto; Forgerini, Fabricio Luchesi (Scientia Plena, 2017)
In this work we study numerically the effects of the angle of deposition of particles in the growth process of a thin-film generated by aggregation of particles added at random. The particles are aggregated in a random position of an initially flat surface and with a given angle distribution. This process gives rise to a rough interface after some time of deposition. We performed Monte Carlo simulations and, by changing the angle of deposition, we observed different results from the random deposition (RD) model. We measured the usual scaling exponents, namely, the roughness () and the growth () exponents. Our results show that the particles added non-perpendicularly to the substrate, can change the behavior in a discrete atomistic random deposition model. When particles are deposited with an angle of 45° in relation to the surface, the values of and  are observed in the Random Deposition model. We also propose an analytic approach, using a differential stochastic equation to analyze the growth process evolution, and our theoretical results corroborate the computer simulations.